Pengaruh Persepsi tentang Sanksi Perpajakan dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Saefulloh, Ridwan; Indarti, Iin (Jurnal Ilmiah Aset, 2012)
This study aims to examine the effect of perceptions of tax sanctions and awareness of taxpayers on taxpayer compliance in Kelurahan Pandansari Semarang. This research is a survey research. The type of data used is primary data with a sample of 85 respondents. Data were analyzed using multiple regression analysis. The results show that the perception of tax sanctions does not affect taxpayer compliance, while the awareness of taxpayers has a positive effect on taxpayer compliance